Automated Extraction of Cranial Landmarks from Computed Tomography Data using a Combined Method of Knowledge and Pattern Based Approaches - Rajapakse, R.N.; Sandaruwan, D.; Karunaratna, D.D.; Samaraweera, S.; Vidanapathirana, M. (Applied Medical Informatics, 2016)
Attached
Keywords: Computed Tomography (CT); Pattern recognition; Contour Template matching; OpenCV